Consequences of clear-cutting and drought on fine root dynamics down to 17 m in coppice-managed eucalypt plantations - Germon, Amandine [UNESP]; Jourdan, Christophe; Bordron, Bruno; Robin, Agnès; Nouvellon, Yann; Chapuis-Lardy, Lydie; de Moraes Gonçalves, José Leonardo; Pradier, Céline; Guerrini, Iraê Amaral [UNESP]; Laclau, Jean-Paul [UNESP] (Elsevier, 2019)
Improving our understanding of the spatiotemporal dynamics of fine roots in deep soil layers is of utter importance to manage tropical planted forests in a context of climate change. Our study aimed to assess the effect of clear-cutting and drought on fine-root dynamics down to the water table in Brazilian ferralsol under eucalypt plantations conducted in coppice. Fine roots (i.e. diameter <2 mm)were sampled down to 17 m deep in a throughfall exclusion experiment comparing stands with 37% of throughfall excluded by plastic sheets (−W)and stands without rain exclusion (+W). Root dynamics were studied using minirhizotron in two permanent pits down to 17 m deep, over 1 year before clear-cutting, then over 2 years in coppice, as well as down to 4 m deep in a non-harvested plot (NH)serving as a control. After harvesting, a spectacular fine root growth of trees conducted in coppice occurred in very deep soil layers (>13 m)and, surprisingly, root mortality remained extremely low whatever the depth and the treatment. Total fine-root biomass in coppice down to 17 m depth was 1266 and 1017 g m−2 in +W and −W, respectively, at 1.5 year after the clear-cut and was 1078 g m−2 in NH 7.5 years after planting. Specific root length and specific root area were about 15% higher in −W than in +W. Proliferation of fine roots at great depths could be an adaptive mechanism for tree survival, enhancing the access to water stored in the subsoil. The root system established before clear-cutting provides access to water stored in very deep layers that probably contribute to mitigate the risk of tree mortality during prolonged drought periods when the eucalypt plantations is conducted in coppice after the clear-cut.
Keywords: Brazil; Coppice; Deep ferralsol profile; Deep root growth; Eucalyptus grandis; Minirhizotron; Throughfall exclusion